Diversity of Arbuscular Mycorrhizal Fungi in the Rhizosphere of Xanthostemon petiolatus (Valeton) Peter G. Wilson at the Halu Oleo University Botanical Garden, Kendari - Husna Husna; La Ode Bin Lacang; Faisal Danu Tuheteru; Asrianti Arif; Wiwin Rahmawati Nurdin (Journal of Tropical Mycorrhiza, 2026)
Arbuscular mycorrhizal fungi (AMF) are one type of mycorrhizal association with plant roots. AMF have a fungal structure in the form of arbuscules, vesicles, and hyphae, which are found in roots and spores in the soil. The research aimed to determine the diversity of arbuscular mycorrhizal fungi on the rhizosphere of Xanthostemon petiolatus in the Botanical Gardens of Universitas Halu Oleo (UHO), Kendari. Studies that have been conducted show that Nona wood has a symbiotic relationship with AMF. The soil and plant root sampling method was carried out at the Botanical Gardens UHO Kendari, randomly (non-proportionally) based on the distribution of plants. Isolated plant roots and identification of AMF were carried out at the Plastic House of the Indonesian Mycorrhiza Association (AMI) Kendari Branch, Southeast Sulawesi Province, which took place during May-June 2024. The results of the research showed that X. petiolatus roots were colonized by AMF, as evidenced by the discovery of internal hyphae and external hyphae. A total of 6 species of AMF from the genus Glomus (5 species) and the genus Acaulospora (1 species) were found. The dominant type is Glomus. Diversity is included in the low category (H ' = 0.235). This type of AMF has the potential to be developed as a biofertilizer.